Relationship between experienced compassion outcomes, burnout and health-related behaviour among psychologists - Aukštinaitytė, R.; Zajančkauskaitė-Staskevičienė, L. (Psichologija, 2010)
The profession of psychologist is based on compassion which may have positive and negative outcomes for a professional. The energy of compassion can be transformed either into fatigue or into satisfaction, depending on the psychologist’s skills to increase affect, resources, and self-care as well as to maintain a balance between personal and professional life. Compassion satisfaction is about the pleasure a psychologist derives from being able to do work well and feeling a pleasure to help others. Compassion fatigue is a direct result of exposure to client’s suffering and complicated by a lack of support in the workplace. Burnout is not directly related to compassion but associated with feelings of hopelessness and difficulties in dealing with conflicts between professional standards and personal feelings and values. Self-care is a potential mechanism to increase the positive and reduce negative outcomes of work on psychologists’ well-being. The aim of the study was to assess the relationship between compassion fatigue, compassion satisfaction and burnout as well as correlations of these constructs with health-related behaviour among psychologists. 103 psychologists took part in the study. The Professional Quality of Life Scale (ProQOL, Stamm, 1999–2000), Self Care and Lifestyle Balance Inventory (McKay, 2004) were used. The results have indicated that compassion fatigue positively correlates with burnout (r = 0.725, p < 0.001). In contrast, compassion satisfaction negatively correlates with burnout (r = –0.209, p = 0.035). Also, it has been found that self-care is related with a higher level of compassion satisfaction (r = 0.356, p < 0.001) and with a lower level of compassion fatigue (r = –0.195, p = 0.048). Significant positive correlations have been found among a greater level of compassion satisfaction and sleeping quality, listening to the signals of one’s own body, preservation of good working and communication skills and healthy limits when struggling for onerself, short brakes at work, time spent with trusted people, self-believe and believing in one’s own abilities and satisfaction with important things in life. Compassion fatigue negatively correlates with the ability to leave the working strain behind, hearing the signals of one’s own body, preservation of healthy limits when struggling for oneself and not allowing others to exhaust you and setting real goals of life and systematically reaching them. Positive correlation has been recognized between compassion satisfaction and workload (r = 0.211, p = 0.033). A greater level of compassion satisfaction is also associated with the participants of the study considering themselves believers and church visiting. Additionally positive correlation has been found between psychologists’ burnout and a greater length of time working in education section. Self-care negatively correlates with a greater number of employments.